Computers in Cardiology, 2005 2005
DOI: 10.1109/cic.2005.1588284
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet denoising of the electrocardiogram signal based on the corrupted noise estimation

Abstract: We present in this paper

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 13 publications
0
35
0
Order By: Relevance
“…There are various security systems evolved in the past, which work on iris [1], audio fingerprint [2], personal signatures [3] and facial features [7] to generate secret keys. The use of the electrocardiogram (ECG) signals for security key generation has also been carried out in the past years [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…There are various security systems evolved in the past, which work on iris [1], audio fingerprint [2], personal signatures [3] and facial features [7] to generate secret keys. The use of the electrocardiogram (ECG) signals for security key generation has also been carried out in the past years [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been used to remove these artifacts: in the time-domain [4], [5], [6], [7]; in the frequency-domain [8] and in time-frequency domain [9], [10]. These methods are based on the use of digital filters.…”
Section: Introductionmentioning
confidence: 99%
“…Israel et al [19] have demonstrated the viability of using cardiovascular function for human identification and proposed a set of ECG descriptors to identify individual. Chauakri et al [20] in their work presented an algorithm of filtering the noisy real ECG signal. Alfaouri and Daqrouq [21] proposed a new approach based on the threshold value of ECG signal determination using wavelet transform coefficients.…”
Section: Introductionmentioning
confidence: 99%